2015
DOI: 10.1242/dev.115964
|View full text |Cite
|
Sign up to set email alerts
|

Communication between distant epithelial cells by filopodia-like protrusions during embryonic development

Abstract: Long-range intercellular communication is essential for the regulation of embryonic development. Apart from simple diffusion, various modes of signal transfer have been described in the literature. Here, we describe a novel type of cellular extensions found in epithelial cells of the somites in chicken embryos. These filopodia-like protrusions span the subectodermal space overlying the dorsal surface of the somites and contact the ectoderm. We show that these protrusions are actin-and tubulin-positive and requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 25 publications
6
69
2
Order By: Relevance
“…For example, cytonemes help mediate Hedgehog signaling in fly (Bischoff et al, 2013;Kornberg and Roy, 2014). Similarly, in vertebrate embryos, long filopodia convey Shh in the developing limb bud and Wnt in the dorsal side of somites (Sanders et al, 2013;Sagar et al, 2015). We demonstrated the localization of Shh and Smo around filopodia in somite epithelial cells and provide supporting data for the requirement of filopodia for activation of the Shh signaling pathway (Fig.…”
Section: Role Of Basal Filopodia In Somite Morphogenesissupporting
confidence: 74%
“…For example, cytonemes help mediate Hedgehog signaling in fly (Bischoff et al, 2013;Kornberg and Roy, 2014). Similarly, in vertebrate embryos, long filopodia convey Shh in the developing limb bud and Wnt in the dorsal side of somites (Sanders et al, 2013;Sagar et al, 2015). We demonstrated the localization of Shh and Smo around filopodia in somite epithelial cells and provide supporting data for the requirement of filopodia for activation of the Shh signaling pathway (Fig.…”
Section: Role Of Basal Filopodia In Somite Morphogenesissupporting
confidence: 74%
“…It has previously been reported that dorsal epithelial cells in the somites protrude filopodia toward ectoderm during segmentation (S0 level; Martins et al, 2009) and myotome differentiation (SVIII level; Sagar et al, 2015). Our study demonstrates that ventral somite epithelial cells protrude filopodia toward endoderm (S0 to VI levels, Fig.…”
Section: Spatiomechanical Organization Of Fn Pillars In the Somiteendsupporting
confidence: 72%
“…For instance, myoblast progenitors of flight muscles have been shown to send out cytonemes that contain the Wnt receptor Frizzled (Frz) and contact the Wnt-producing cells in the wing imaginal disc; the resulting Wnt-Frz complexes then move in a retrograde manner along the dynamic myoblast cytonemes (Huang and Kornberg, 2015). Similarly, the Wnt receptor Frz7 has been identified on the filopodia of dermomyotome cells in chicken (Sagar et al, 2015). Taken together, there is increasing evidence, suggesting that a conserved filopodia-based mechanism contributes to the distribution of both Wnt ligands and their receptors during development of vertebrate and invertebrates.…”
Section: Wnt Cytonemes In Developmentmentioning
confidence: 99%
“…Concomitantly, the Wnt receptor Frz was identified on cytonemes to enable the retrograde transport of Wnt proteins on these protrusions during flight muscle formation in Drosophila (Huang and Kornberg, 2015). In chicken, Frz7 was found on extensions that are positive for actin and microtubules during dermomyotome development (Sagar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%